The effects of moisture at baling and wrapping delay on storage characteristics of annual ryegrass round bale silage. Issue 1 (4th April 2020) - Crook, Tyler; Stewart, Brandon; Sims, Michael; Weiss, Caleb; Coffey, Ken; Coblentz, Wayne; Beck, Paul
Abstract: Moisture content and time between baling and wrapping round bale silage impacts silage quality and aerobic stability. The objective of this study was to observe the effects of wrapping delays of 0, 1, 2, or 3 d on the nutritional quality and storage characteristics of annual ryegrass ( Lolium multiflorum Lam.) silage baled at two levels of moisture (30 ± 9.5% [DRY] or 74 ± 0.8% [WET]). The DRY ( n  = 18) and WET ( n  = 20) bales were assigned as replicates and wrapped by pasture quadrant, then stored for 85 d. Crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF), and acid detergent insoluble crude protein (ADICP) of the silage were greater ( P  < .01) for DRY than WET. Wrapping delays did not change bale weight or CP, but dry matter concentrations decreased linearly ( P  = .03) and ADF, NDF, and ADICP increased ( P ≤ .02) linearly with wrapping delay. The maximum temperature of DRY was greater ( P  = .01) than WET and increased linearly with wrapping delays ( P  < .01). Changes in the fermentation profile of WET bales with delays in wrapping indicated altered fermentation and increased pH, which will result in reduced shelf life as well as clostridial activity with greater butyric acid content and possible reduced intake by livestock. Based on these results, ryegrass fermentation patterns and nutritional quality show a decline with each day delayed before wrapping with WET silage.